Hybrid Collision Detection Algorithm based on Image Space - XueLi Shen; Qiong Wu; Yuwei Cheng (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
Collision detection is an important application in the field of virtual reality, and efficiently completing collision detection has become the research focus. For the poorly real-time defect of collision detection, this paper has presented an algorithm based on the hybrid collision detection, detecting the potential collision object sets quickly with the mixed bounding volume hierarchy tree, and then using the streaming pattern collision detection algorithm to make an accurate detection. With the above methods, it can achieve the purpose of balancing load of the CPU and GPU and speeding up the detection rate. The experimental results show that compared with the classic Rapid algorithm, this algorithm can effectively improve the efficiency of collision detection. DOI: http://dx.doi.org/10.11591/telkomnika.v11i12.3744